The Relationship Between Leg Length, Leg Muscle Power, and Flexibility with Shooting Ability in the Futsal Team of SMP N 4 Surakarta - Putra, Aradya Pramudita; Syaifullah, Rony; Adi, Pomo Warih (Java Mutiara Media, 2025)
This study aims to examine the relationship between leg length, leg muscle power, and flexibility with shooting ability in the futsal team of SMP N 4 Surakarta. The research used a quantitative correlational method involving 25 male students as subjects. Data were collected through tests and measurements using a measuring tape, standing broad jump test, sit and reach test, and shooting ability test. Data analysis employed Pearson product-moment correlation and multiple regression using SPSS version 23. The results showed: (1) No significant relationship between leg length and shooting ability (sig. 0.066 > 0.05; r = 0.374). (2) A significant relationship between leg muscle power and shooting ability (sig. 0.001 < 0.05; r = 0.639). (3) A significant relationship between flexibility and shooting ability (sig. 0.004 < 0.05; r = 0.550). (4) A simultaneous significant relationship between leg length, leg muscle power, and flexibility with shooting ability (F = 8.789 > Ftable = 3.07; sig. 0.001 < 0.05), with a contribution of 55.7%. It can be concluded that leg muscle power and flexibility have a significant relationship with shooting ability, while leg length does not have a significant relationship.